Uji aktivitas antibakteri ekstrak n-heksana daun sawo (Manilkara zapota L) terhadap pertumbuhan bakteri Staphylococcus aureus dan Escherichia coli - Manuppak Irianto Tampubolon; Rani Erlianti Br. Hutabarat (Journal of Pharmaceutical and Sciences, 2023)
Sapodilla leaves have active compounds which are often referred to as secondary metabolites, which include alkaloids, flavonaids, saponins, tannins, glycosides, steroids. This study aims to determine the antibacterial activity of sapodilla leaf n-hexane extract (Manilkara zapota L) against Staphylococcus aureus and Escherichia coli bacteria. Tests were carried out through the stages of collecting materials, preparing simplicia, making sapodilla leaf n-hexane extract and testing the inhibition of sapodilla leaves against Staphylococcus aureus and Escherichia coli bacteria. The preparation of sapodilla leaf n-hexane extract was carried out by maceration method using n-hexane. Antibacterial activity testing was carried out by the agar diffusion method using disc paper. The results of the study based on the results of the phytochemical screening showed that the simplicia and n-hexane extract of sapodilla leaves contain alkaloids, flavonoids, saponins, tannins. Meanwhile, in the antibacterial activity test of the sapodilla leaf n-hexane extract, it had antibacterial or inhibition zones on the bacteria with different concentrations, namely concentrations of 35%, 45%, 55%, 65%, and 75%. The positive control used chloramphenicol and the negative control used sterile aquadest. Sapodilla leaf n-hexane extract has antibacterial activity of Staphylococcus aureus and Escherichia coli.